The Effect of Product Advertising Through YouTube Media on Brand Awareness, Brand Image, and Purchase Intentions in the Millennial Generation - Irfandi, Fariz; Abdurrahman, Agus (International Journal of Management Science and Information Technology, 2023)
This study aims to see the influence of YouTube media as a place for promoting or advertising various products on brand awareness, brand image, and purchase intention by millennials in Indonesia. This research is based on advertising value theory and generational cohort theory. The variables in this study are YouTube advertising, brand awareness, brand image, and purchase intention. This study used a quantitative approach by distributing questionnaires online which managed to get 141 respondents. The respondents were collected by convenience sampling technique based on the choice of age criteria ranging from 18 years to 40 years the birth of the millennial generation 1982-2004 was based on the theory of generation by Strauss-Howe and using YouTube as an entertainment medium and information channel. Process the data from the results of this study using the PLS-SEM application. The results of this study found that there was a positive influence of YouTube advertising on brand awareness, brand image, and direct purchase intention. Brand image also influences purchase intention, but brand awareness does not influence purchase intention. So only brand image can be said as a mediating variable, while brand awareness is not. This research can be additional literacy related to the topic of the influence of YouTube advertisements which is still small. Companies can use this research as a basis for studies to make product or brand marketing through digital media more attractive to convey to consumers.